Can Phone-Based Motivational Interviewing Improve Medication Adherence to Antiplatelet Medications After a Coronary Stent Among Racial Minorities? A Randomized Trial - Palacio, Ana M.; Uribe, Claudia; Hazel-Fernandez, Leslie; Li, Hua; Tamariz, Leonardo J.; Garay, Sylvia D.; Carrasquillo, Olveen (Journal of general internal medicine : JGIM, 2015)
ABSTRACT BACKGROUND Minorities have lower adherence to cardiovascular medications and have worst cardiovascular outcomes post coronary stent placement OBJECTIVE The aim of this study is to compare the efficacy of phone-delivered Motivational Interviewing (MINT) to an educational video at improving adherence to antiplatelet medications among insured minorities. DESIGN This was a randomized study. PARTICIPANTS We identified minorities with a recently placed coronary stent from an administrative data set by using a previously validated algorithm. INTERVENTIONS MINT subjects received quarterly phone calls and the DVD group received a one-time mailed video. MAIN MEASURES Outcome variables were collected at baseline and at 12-month post-stent, using surveys and administrative data. The primary outcome was antiplatelet (clopidogrel and prasugrel) adherence measured by Medication Possession Ratio (MPR) and self- reported adherence (Morisky score). We also measured appropriate adherence defined as an MPR ≥ 0.80. KEY RESULTS We recruited 452 minority subjects with a new coronary stent (44 % Hispanics and 56 % Black). The patients had a mean age of 69.5 ± 8.8, 58 % were males, 78 % had an income lower than $30,000 per year and only 22 % had achieved high school education or higher. The MPR for antiplatelet medications was 0.77 for the MINT group compared to 0.70 for the DVD group ( p < 0.05). The percentage of subjects with adequate adherence to their antiplatelet medication was 64 % in the MINT group and 50 % in the DVD group ( p < 0.01). Self-reported adherence at 12 months was higher in the MINT group compared to the DVD group ( p < 0.01). Results were similar among drug-eluting stent (DES) recipients. CONCLUSIONS Among racial minorities, a phone-based motivational interview is effective at improving adherence to antiplatelet medications post coronary stent placement. Phone-based MINT seems to be a promising and cost-effective strategy to modify risk behaviors among minority populations at high cardiovascular risk.